Elaboración de una propuesta de reestructuración de los procesos de apoyo que impactan los costos de la compañía COLREGISTROS S.A.S. (2015)
Given the current market needs of the hydrocarbon sector, in which cost restructuring is required in order to keep the companies in the sector afloat, cost reduction strategies must be proposed from all processes. This degree work focused on obtaining a cost restructuring proposal from the company's support processes so that, from these processes, adequate control is given to the critical tasks that are currently generating costs in the company. organization; For this purpose, the management, administration, human resources and procurement processes were evaluated, from the cost side, as summarized below: Management process: it is proposed to revise the strategic direction of the company from its vision and mission, proposing long-term sustainability goals and metrics of control of budgets, income, profitability and effectiveness in the presentation of proposals that allow to measure and control the progress of the company towards the goals and objectives established in the organization. Administrative Process: Focus on accompanying management on cost control for projects in key activities such as presentation of proposals, control of inventories, travel expenses and per diems that are handled from the smaller boxes and the proper use of resources physical in terms of plants and equipment. Purchasing Processes: It is proposed to revise the purchasing system ensuring transparency and efficiency in acquisitions from source to delivery. In this way, the process must ensure that suppliers comply with the requirements for the provision of the service. Human Management Process: The process starts from the selection and hiring where it should be checked if there is a strict control for the assignment of the type of contract according to the profile of the same, that there is adequate control of payroll payment according to contracting and approval concepts by the corresponding areas. It was reviewed if it is convenient that other processes of the company are included in the process map, since currently the company does not have documented processes such as treasury, accounting and IT, processes that are in the knowledge of the people who execute them and of which there is no record of procedures, nor control. To the extent that the company can come up with an adequate address and execute the necessary control to reduce costs for reprocessing, making bad decisions and seeking a continuous improvement, it could save money and become more productive and sustainable in the time.